Synergetic enhancement in optical nonlinearity of Au nanoparticle decorated MoS2 via interaction between excitonic and surface plasmon resonances - Park, Byeongho; Lee, Donggeun; Kim, Hyo-suk; Cho, Youngho; Park, Subeen; Kim, Chulki; Lee, Taikjin; Woo, Deok Ha; Kim, Jae Hun (ELSEVIER, 2020)
Local intensive field by surface plasmon resonance on gold nanoparticles boosted the nonlinear property of MoS2. Au decorated MoS2 nanohybrid material was prepared using facile photo-chemical method with MoS2 dispersion and HAuCl4 to create Au nanoparticles specifically at the edge of MoS2 sheets. The prominent nonlinear features of samples was investigated by Z-scan measurement and supercontinuum generation. The Au and MoS2 nanohybrid provided outstanding nonlinear refractive index, n(2), of 1.45 x 10(-5) cm(2)/W and the third-order nonlinear susceptibility, x((3)), of 8.18 x 10(-3) esu, which were about four times larger than those of intrinsic MoS2. The excitonic resonance in MoS2 shows the synergetic interaction with surface plasmon resonance of Au nanoparticles at the edge, which results in concentrated nonlinear process with strong plasmonic field by localization and polarity. The hollow core fiber with optical bandgap was employed to make the supercontinuum generation from sample materials. From the 3-cm short fiber filled with Au decorated MoS2, the broad spectrum covering whole visible and near-infrared range was obtained, while that with MoS2 only exhibited emission about 200 nm of bandwidth. Our nanohybrid material and filament will be an important aspect in exploring nonlinear optical properties for the combination of transition-metal dichalcogenides and metal nanoparticles.
Keywords: SUPERCONTINUUM GENERATION; MOLYBDENUM-DISULFIDE; THIN-FILMS; DISPERSIONS; SPECTRA; BULK; SIZE; WS2